International Education Programs and Political Influence : Manufacturing Sympathy? - Wilson, Iain; SpringerLink (Online service) (New York : Palgrave Macmillan US, 2014)
Exchange programs are often considered to create goodwill for host countries among foreign citizens - yet is this the case? Drawing on a wealth of research with participants and alumni of exchange programs, Iain Wilson shows that the pursuit of goodwill receives little return and distracts these programs from the benefits they are able to deliver.
Keywords: Science; Science, general